Tissue Engineering: 3D Printing of Personalized Thick and Perfusable Cardiac Patches and Hearts (Adv. Sci. 11/2019) - Noor, Nadav (Adv Sci (Weinh), 2019)
In article number 1900344, Tal Dvir and co‐workers take a biopsy of an omental tissue from patients. While the cells are reprogrammed to induced pluripotent stem cells and differentiate into cardiomyocytes and endothelial cells, the remaining extracellular matrix is processed into a thermoresponsive hydrogel. These personalized materials and cells are used as bioinks to print functional vascularized cardiac patches and small‐scale human hearts. [Image: see text]